PENGARUH LIFESTYLE, BRAND IMAGE, BRAND AWARENESS DAN KUALITAS PRODUK TEHADAP KEPUTUSAN PEMBELIAN IPHONE(STUDI PADA MAHASISWA/MAHASISWI DI PURWOKERTO) - Putri Nur Amira; Herni Justiana Astuti; Wida Purwidianti; Arini Hidayah (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to analyze the influence of Lifestyle, Brand Image, Brand Awareness, and Product Quality on iPhone purchasing decisions among college students in Purwokerto. The research was conducted using a quantitative approach with a survey method through questionnaires distributed to 108 students from three universities. Data analysis employed validity and reliability tests, multiple linear regression, F-tests, and t-tests using SPSS version 25. The results indicate that brand image and product quality have a significant effect on purchasing decisions, while lifestyle and brand awareness do not show significant effects. The regression model obtained an Adjusted R Square of 0.572, meaning that 57.2% of purchasing decisions are explained by the four variables studied. These findings suggest that rational cognitive evaluation through product quality and emotional affective responses related to brand image are dominant factors influencing iPhone purchasing decisions among students in Purwokerto.